KAJI EKSPERIMENTAL PENGARUH TEMPERATUR BIODIESEL MINYAK SAWIT TERHADAP PERFORMANSI MESIN DIESEL DIRECT INJECTION PUTARAN KONSTAN - Fajar, Berkah; Utomo, Tony Suryo; Murni, Murni (ROTASI, 2009)
The imperfect combustion process will be a problem in the development effort of diesel engine’sperformance. Nonhomogen air–fuel mixing process is one of the factors which cause the imperfectcombustion.By heating up the diesel biodiesel up to a certain temperature before it goes through thehigh pressure injection pump will lower its density and viscosity. Therefore, when injected in thecombustion chamber, it will formed smaller droplets of fuel spray which result in a morehomogenious air–fuel mixture. Also by using higher temperature will make the diesel fuel easier toignite in order to compensate the limited time which is available in high speed operating conditions.Diesel engine Dong Feng 1 cylinder direct injection at constant speed was used in this research. Thefuel used are biodiesel with temperature variations in the range from 33oC to 90oC . The best thermalefficiency for biodiesel fuel is 25.3 % at 70oC with 28 % BSFC. In this condition, the fuelconsumption was decreased 8 % by comparing with that at 33oC.